Long-Term Impact of Direct-Acting Antivirals on Liver Fibrosis and Survival in HCV-Infected Liver Transplant Recipients - Martina Gambato; Chiara Manuli; Erica N. Lynch; Sara Battistella; Giacomo Germani; Marco Senzolo; Alberto Zanetto; Alberto Ferrarese; Alessandro Vitale; Enrico Gringeri; Umberto Cillo; Patrizia Burra; et al. (Viruses, 2023)
(1) Background: Little is known about the long-term impact of sustained virological response (SVR) on fibrosis progression and patient survival in liver transplantation (LT) recipients treated with direct-acting antivirals (DAAs). We investigated liver fibrosis evolution and patient survival in hepatitis C virus (HCV)-infected patients receiving DAAs after LT. (2) Methods: All consecutive HCV-infected patients treated with DAAs after LT between May 2014 and January 2019 were considered. The clinical and virological features were registered at the baseline and during the follow-up. The liver fibrosis was assessed by liver biopsy and/or transient elastography (TE) at the baseline and at least 1 year after the end of treatment (EoT). (3) Results: A total of 136 patients were included. The SVR12 was 78% after the first treatment and 96% after retreatment. After the SVR12, biochemical tests improved at the EoT and remained stable throughout the 3-year follow-up. Liver fibrosis improved after the SVR12 (p < 0.001); nearly half of the patients with advanced liver fibrosis experienced an improvement of an F ≤ 2. The factors associated with lower survival in SVR12 patients were the baseline platelet count (p = 0.04) and creatinine level (p = 0.04). (4) Conclusions: The long-term follow-up data demonstrated that SVR12 was associated with an improvement in hepatic function, liver fibrosis, and post-LT survival, regardless of the baseline liver fibrosis. The presence of portal hypertension before the DAAs has an impact on patient survival, even after SVR12.